Enhancing Cross-Border Justice: Facilitating Asset Recovery from Corruption Between Indonesia and Australia Through Mutual Legal Assistance - Setiyono, Joko; Quiko, Eduard; Putri, Andini Kusuma; Hartono, Darminto (Universitas Negeri Semarang, 2024)
The level of corruption crimes that are committed in today's society is growing from year to year, and it is accompanied by other types of criminal activity, such as the concealment of assets that result from corruption in other countries. In order to eradicate a variety of crimes that have a transnational character, particularly corruption, one of the actions that can be made is to take assets that have been developed due to corruption in other countries. This can be done through Mutual Legal Assistance. Regulations about MLA have been enacted due to the passage of Law Number 1 of 2006, which discusses providing mutual assistance in criminal matters. Mutual Legal Assistance is considered to be the first stage of law enforcement, particularly in the process of recovering state assets that have been stolen as a result of corruption crimes. As a result, cooperation with other nations is required, such as the cooperation between Indonesia and Australia, which aims to return state assets that have been stolen due to corruption crimes hidden in Australia.